Baseline Quality of Life before Intensive Care: A Comparison of Patient versus Proxy Responses - Gifford, Jeneen M. (2010)
OBJECTIVE: To compare acute lung injury (ALI) patients’ self-reported, retrospective baseline quality of life (QOL) before their intensive care hospitalization with population norms and retrospective proxy estimates. DESIGN: Prospective cohort study using the Short Form 36 (SF-36) QOL survey. SETTING: 13 intensive care units at 4 teaching hospitals in Baltimore, MD, USA. PATIENTS: 136 ALI survivors and their designated proxies. INTERVENTIONS: Both patients and proxies were asked to estimate patient baseline QOL before hospital admission using the SF-36 survey. MEASUREMENTS AND MAIN RESULTS: Compared to population norms, QOL scores were lower in ALI patients across all 8 domains, but the difference was significantly greater than the minimum clinically important difference in only 2 of 8 domains (Physical Role and General Health). The mean paired difference between patient versus proxy responses revealed no clinically important difference. However, kappa statistics demonstrated only fair to moderate agreement for all domains. Bland-Altman analysis revealed that for all domains, proxies tended to overestimate QOL when patient scores were low and underestimate QOL when patient scores were high. CONCLUSION: Retrospective assessment of QOL prior to hospitalization revealed that ALI patients were consistently lower than population norms, but the magnitude of this difference may not be clinically important. Proxy assessments had only fair to moderate agreement with patient assessments. Across all 8 SF-36 QOL domains, proxy responses represented an attenuation of patient QOL estimates.